2021
DOI: 10.1080/07391102.2021.1973563
|View full text |Cite
|
Sign up to set email alerts
|

Discovery of potential SARS-CoV 3CL protease inhibitors from approved antiviral drugs using: virtual screening, molecular docking, pharmacophore mapping evaluation and dynamics simulation

Abstract: The spread of corona-virus disease 2019 (COVID-19) has been faster than any other corona-viruses that have succeeded in crossing the animal-human barrier. This disease, caused by the severe acute respiratory syndrome corona-virus 2 (SARS-CoV-2/2019-nCoV) posing a serious threat to global public health and local economies. There are three responsible for this disease; SARS-CoV-2, SARS-CoV and MERS-CoV. Whereas our goal is to test the affinity for a new class of compounds obtained from a hybridization of Chloroq… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(4 citation statements)
references
References 96 publications
0
3
0
Order By: Relevance
“…The molecular docking studies were carried out to identify the binding interactions of the most active compounds 2 and 8 within the binding site residue of the targets by using MOE software [46], and the docking protocol steps were followed and detailed in our previous research [47,48] The re-dock of all native ligands to their targets was conducted using "Dock Option" implemented in the MOE software [46] to validate the used method. The RSMD values of the obtained complexes (Targets-Crystallized ligands) were less than 2.50 Å [49], meaning that the docking method is accurate and successful.…”
Section: Docking Methods Protocol and Validationmentioning
confidence: 99%
“…The molecular docking studies were carried out to identify the binding interactions of the most active compounds 2 and 8 within the binding site residue of the targets by using MOE software [46], and the docking protocol steps were followed and detailed in our previous research [47,48] The re-dock of all native ligands to their targets was conducted using "Dock Option" implemented in the MOE software [46] to validate the used method. The RSMD values of the obtained complexes (Targets-Crystallized ligands) were less than 2.50 Å [49], meaning that the docking method is accurate and successful.…”
Section: Docking Methods Protocol and Validationmentioning
confidence: 99%
“…The docking procedure has been described earlier. [44][45][46] The PDB file -1SA0 was downloaded from the Protein Data Bank for the three dimensional structure of tubulin. First, the 3D Structures of test compounds, 1 a-d, 3 a-c, and 4 a-c were built with MOE software, and we minimized them by using the MMFF94x force-field with reaction-field electrostatics (Din = 1, Dout = 80) using a flat bottom tether (10.0 kcal/ mol, 0.25 Å), which was applied to all atoms.…”
Section: Methodsmentioning
confidence: 99%
“…The software source was The Chemical Computing Group Inc., Montreal, QC, Canada. The docking procedure has been described earlier [44–46] . The PDB file – 1SA0 was downloaded from the Protein Data Bank for the three dimensional structure of tubulin.…”
Section: Methodsmentioning
confidence: 99%
“…In many earlier studies it has been observed that the highest dock score achieved by molecular docking does not imply that the molecule is a potent lead; until molecular dynamics simulations are required to validate this conclusion [46]. To determine the stability of the proteins and ligandprotein complexes, molecular dynamics simulations were used [47].…”
Section: Molecular Dynamics Simulationsmentioning
confidence: 99%